2017
DOI: 10.3390/ijms18040850
|View full text |Cite
|
Sign up to set email alerts
|

Pannexin- and Connexin-Mediated Intercellular Communication in Platelet Function

Abstract: The three major blood cell types, i.e., platelets, erythrocytes and leukocytes, are all produced in the bone marrow. While red blood cells are the most numerous and white cells are the largest, platelets are small fragments and account for a minor part of blood volume. However, platelets display a crucial function by preventing bleeding. Upon vessel wall injury, platelets adhere to exposed extracellular matrix, become activated, and form a platelet plug preventing hemorrhagic events. However, when platelet act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 166 publications
(209 reference statements)
0
17
0
Order By: Relevance
“…After stable adhesion, the platelets are activated and induce intracellular calcium flux to release α granules and dense granules, including 5-hydroxytryptamine, adenosine diphosphate, and adenosine triphosphate, for amplification of the platelet response. The α-granules include thromboxane A2, leukotriene B4 (LTB4), and a variety of pro-inflammatory mediators [ 148 ], which affect SMCs, endothelial cells, and promote cross-talk between monocytes and macrophages [ 149 , 150 ]. The release of IL-1β and expression of CD-40L induce endothelial cells to produce IL-6, IL-8, MCP-1, and ROS, as well as the upregulation of leukocyte-adhesion molecules.…”
Section: Plaque Rupture and Platelet Activationmentioning
confidence: 99%
“…After stable adhesion, the platelets are activated and induce intracellular calcium flux to release α granules and dense granules, including 5-hydroxytryptamine, adenosine diphosphate, and adenosine triphosphate, for amplification of the platelet response. The α-granules include thromboxane A2, leukotriene B4 (LTB4), and a variety of pro-inflammatory mediators [ 148 ], which affect SMCs, endothelial cells, and promote cross-talk between monocytes and macrophages [ 149 , 150 ]. The release of IL-1β and expression of CD-40L induce endothelial cells to produce IL-6, IL-8, MCP-1, and ROS, as well as the upregulation of leukocyte-adhesion molecules.…”
Section: Plaque Rupture and Platelet Activationmentioning
confidence: 99%
“…The lack of chemical compounds that selectively act on Panx1 channel gating hampers Panx1 research. Currently used pharmacological Panx1 blockers, such as carbenoxolone, mefloquine and probenecid, often also block connexin channels or act on purinergic receptors [25,26]. The best option seems to be 10 Panx1, an EL1 mimetic peptide that impedes the passage of small molecules and ATP through the Panx1 channel [27].…”
Section: Blocking Panx1 Channels Delays Hemostasis and Thrombosis In mentioning
confidence: 99%
“…3D,E), demonstrating the feasibility of altering the hemostatic balance in vivo by compounds acting on Panx1 channels. Importantly, BB-FCF is rapidly excreted from the body and does not seem to display (serious) side-effects either [25]. However, similar to other pharmacological Panx1 inhibitors, the Panx1 specificity of BB-FCF has recently been called into question by studies showing that high concentrations of the dye can directly inhibit P2X receptors [31], and it can thus not be excluded that the in vivo effects of BB-FCF on hemostasis may be partly driven by inhibition of P2X7 receptors expressed in the endothelium.…”
Section: Blocking Panx1 Channels Delays Hemostasis and Thrombosis In mentioning
confidence: 99%
“…Recent analysis of the megakaryocyte (and therefore the platelet) channelome revealed that among a range of cell surface channel proteins, Panx1 is also likely to be expressed. A series of pharmacological approaches using selective mimetic peptide inhibitor [ 175 ], subsequently confirmed using Panx1-deficient mouse platelets [ 176 ], demonstrated this protein to contribute to calcium responses to low concentrations of various platelet agonists. The ability of Panxs to facilitate the release of ATP from cells is a property that has also been observed in platelets.…”
Section: Connexins and Pannexins In The Control Of Platelet Functimentioning
confidence: 99%
“…The ability of Panxs to facilitate the release of ATP from cells is a property that has also been observed in platelets. Panx1 mediated ATP release results in subsequent stimulation of the ATP-gated calcium channel P2X1, which causes enhanced calcium influx and therefore propagation of platelet functional responses [ 175 , 176 ]. At higher concentrations of collagen or other platelets agonists P2X1 makes little contribution to cell responses, and therefore the effects of Panx1 are restricted to conditions where agonist concentrations are limited.…”
Section: Connexins and Pannexins In The Control Of Platelet Functimentioning
confidence: 99%